Early Satiety in Cancer: A Clinical Review of Definition and Therapeutic Management - Telford, Brittany; Condon, Therese; Flynn, Breanna; Cassidy, Jane; Feely, Olwyn; Murphy, Gearoid; O’Gara, Ruth; Sparrow, Rachel; Barrett, Michelle; Walsh, Declan (Trinity Student Medical Journal, 2020)
Early satiety is defined as the desire to eat with the inability to eat appropriate amounts due to premature fullness. Although a common symptom of cancer, it is rarely recognised in medical practice and poorly elucidated in the literature. This review highlights the importance of early satiety in cancer, and outlines appropriate treatment. A literature search was conducted using EMBASE, CINAHL and SCOPUS. The search was limited to articles available in English and peer-reviewed journals. Articles were screened in four stages by two independent reviewers and the Preferred Reporting Items for Systematic Reviews (PRISMA) was used. 486 articles were identified, of which, five full-text articles were included in the study. The literature outlined that targeting central and peripheral mechanisms are key to symptom management. Peripherally-acting prokinetics such as metoclopramide are considered first line therapy. Agents that target gastric accommodation such as clonidine, sumatriptan and sildenafil may also be useful. Centrally acting pharmacological agents associated with digestion may be effective. Centrally acting agents include: progesterone receptor agonists, cannabinoids and ghrelin agonists. Overall, early satiety is an under-recognised, but important symptom in cancer. Due to the limited studies available, the efficacy of treatments are not well established. High quality studies outlining appropriate therapeutic management are necessary to establish standardised treatment protocols.